A Novel Regulator of Preadipocyte Differentiation, Transcription Factor TCF21, Functions Partially Through Promoting LPL Expression - Zhang, Xinyang; Cheng, Bohan; Liu, Chang; Du, Zhiqiang; Zhang, Hui; Wang, Ning; Wu, Mengqi; Li, Yumao; Cao, Zhiping; Li, Hui (Frontiers in Physiology, 2019)
The transcription factor TCF21 has been previously shown to be specifically expressed in white preadipocytes in mice. However, the exact biological function of TCF21 in the context of adipogenesis remains unknown. In the current study, we used chicken lines selected based on their abdominal fat content, and observed a significant decrease in TCF21 mRNA and protein levels in the abdominal fat of lean broilers relative to fat broilers. Moreover, TCF21 expression increased throughout preadipocyte differentiation in vitro. We also found that TCF21 knockdown and over-expression attenuated and promoted preadipocyte differentiation, respectively, as evidenced by appropriate changes in lipid droplet accumulation and altered expressions of C/EBPa, LPL, and A-FABP. Additional chromatin immunoprecipitation analyses and luciferase assays demonstrated that TCF21 promotes the transcription of LPL by directly binding to the E-box motif in the LPL promoter. Together, these results show that TCF21 is a novel regulator of preadipocyte differentiation, in part by directly promoting LPL expression.